Humans as a model species for sexual selection research. Issue 1866 (8th November 2017) - Wilson, Michael Lawrence; Miller, Carrie M.; Crouse, Kristin N.
Abstract : Ever since Darwin, questions about humans have driven sexual selection research. While studies of other organisms are often justified as useful for improving understanding of humans, humans themselves can be useful models. Although humans present some drawbacks as model organisms (complicated societies, slow reproduction and strong ethical constraints on experimental options), humans nonetheless offer many advantages (being abundant, accessible and having detailed historical records for some populations). As an additional challenge, humans exhibit a rather puzzling combination of traits. Some traits (pair-bonding, biparental care and modest sexual dimorphism in body size) suggest selection for monogamous mating, while other traits (including sexual dimorphism in body composition and appearance) suggest selection for polygyny. Such puzzles have motivated research on other species, resulting in a rich set of comparative data that provides insights into humans and other species. Recent studies of visual trait dimorphism suggest that human appearance reflects adaptation for multi-level societies, rather than high levels of polygyny. In addition to biological traits, human cultural traits have undergone rapid evolution. Changes in subsistence strategies profoundly affect opportunities for sexual selection. The enormous variability of human behaviour and ecology provides abundant opportunities to test key hypotheses, and poses challenging puzzles for future research.